Airway epithelial cell-specific deletion of EGFR modulates mucoinflammatory features of cystic fibrosis-like lung disease in mice - Choudhary, Ishita; Paudel, Kshitiz; Kumar, Rahul; Sharma, Amit; Patial, Sonika; Saini, Yogesh (Frontiers in Immunology, 2025)
Mucoinflammatory lung disease in cystic fibrosis (CF) is characterized by airway surface liquid (ASL) layer dehydration and mucins hyperconcentration, which leads to airway obstruction, inflammation, bronchiectasis, and increased susceptibility to recurrent bacterial infections. Epidermal growth factor receptor (EGFR) is known to regulate airway mucous cell metaplasia (MCM) and mucins expression, but the role of EGFR pathway in the pathogenesis of CF-like lung disease remains unclear. Therefore, we hypothesized that airway epithelial cell-specific deficiency of EGFR mitigates mucoinflammatory responses in Scnn1b-transgenic (Tg+) mice that phenocopy human CF-like lung disease. To test this hypothesis, we examined the effect of airway epithelial cell-specific EGFR deficiency on the manifestation of mucoinflammatory outcomes in Tg+ mice. The airway epithelial cell-specific EGFR-deficient wild-type (WT) mice did not exhibit any obvious structural and functional defects in the lungs. The deletion of EGFR in airway epithelial cells in Tg+ mice, however, resulted in increased recruitment of neutrophils and macrophages into the lung airspaces, which was accompanied by significantly increased bronchoalveolar lavage fluid (BALF) levels of inflammatory mediators, including KC, G-CSF, MIP-2, MIP-1α, TNF-α, and MIP-1β. Additionally, as compared with the EGFR-sufficient Tg+ mice, the airway epithelial cell-specific EGFR-deficient Tg+ mice exhibited significantly increased postnatal mortality and compromised bacterial clearance. The deletion of EGFR in the airway epithelial cells of Tg+ mice resulted in an increased degree of mucus obstruction, which was associated with an increase in MCM and MUC5B production. Some of the molecular markers of type 2 inflammation, including Il13, Slc26a4, and Retnla, were significantly increased in airway epithelial cell-specific EGFR-deficient Tg+ mice versus EGFR-sufficient Tg+ mice. Taken together, our data show that EGFR deletion in the airway epithelial cells compromises postnatal survival, delays bacterial clearance, and modulates inflammatory and mucus obstruction-relevant endpoints, i.e., MCM, MUC5B production, and mucus obstruction, in Tg+ mice.